The effects of independent directors’ financial knowledge and external directorships on firm performance - Hamezah Md Nor,; Intan Maiza Abd Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Prior studies have provided some inconclusive findings regarding the effect of independent directors (INEDs) on firm performance. Drawing insights from the theories of resource dependence (RD), human capital (HC), and social capital (SC), this research argues that the mere presence of INEDs (motivation) is insufficient but rather the appointed INEDs need to have sufficient HC and SC (ability) in the forms of knowledge, expertise, and connection to effectively perform their roles. This study extends prior research by investigating the effects of INEDs’ financial knowledge (as indicator of INEDs’ HC) and INEDs’ external directorship (as indicator of INEDs’ external SC) on firm performance. A total of 300 non-financial firms listed on Bursa Malaysia in the year 2013 were selected using stratified random sampling method. Results indicated that INEDs’ financial knowledge does not have any relationship with firm performance. In contrast, an inverted U-shaped relationship between INEDs’ external directorship and firm performance was found, hence reflecting a trade-off between SC gain through external directorship and busyness effect. The findings of this research suggest that there are potential costs and benefits associated with INEDs’ SC. The findings also support the call for limiting the number of directorship an INED can have.